Measuring Epistemic Deliberation on Polarized Issues: The Case of Abortion Provision in Ireland. (November 2022) - Suiter, Jane; M Farrell, David; Harris, Clodagh; Murphy, Philip
This paper compares the debate quality in the plenary sessions of an Irish Citizens' Assembly and an Irish parliamentary committee to assess the epistemic effects of public deliberation on a contentious subject: abortion. The unusual occurrence of a similar process of detailed discussion on the same topic in different institutions at around the same time (in 2016–2017) allows us to compare the deliberative capacities of these institutions and thus contribute to discussions on the appropriateness of an increasingly debated democratic reform: assigning political offices by lot. We suggest that the epistemic effect of deliberation on abortion should facilitate nuanced multi-layered discussion that is both 'deeper' in being based on multi-faceted arguments and 'wider' in terms of a more accommodative view. We anticipate that these effects should be more pronounced in the more deliberative, less polarized, environment of a citizens' assembly rather than in a parliamentary committee. The analysis deploys the psychological concept of 'cognitive complexity'. We find that members of the Citizens' Assembly demonstrate a deeper cognitively complex grasp of the subject matter. In contrast, experts and parliamentarians tend to adjust their mode of delivery at a parliamentary committee reflecting the conflictual and strategic aspects of political debates in such a forum.